Molecular signature associated with cladribine treatment in patients with multiple sclerosis - Fissolo, Nicolas; Calvo-Barreiro, Laura; Eixarch, Herena; Boschert, Ursula; Villar, Luisa M.; Costa-Frossard, Lucienne; Ferrer, Mireia; Sanchez, Alex; Borràs, Eva; Sabidó, Eduard; Espejo, Carmen; Montalban, Xavier; et al. (Frontiers in Immunology, 2023)
Little is known about the molecular profiling associated with the effect of cladribine in patients with multiple sclerosis (MS). Here, we aimed first to characterize the transcriptomic and proteomic profiles induced by cladribine in blood cells, and second to identify potential treatment response biomarkers to cladribine in patients with MS.Methods: Gene, protein and microRNA (miRNA) expression profiles were determined by microarrays (genes, miRNAs) and mass spectrometry (proteins) in peripheral blood mononuclear cells (PBMCs) from MS patients after in vitro treatment with cladribine in its active and inactive forms. Two bioinformatics approaches to integrate the three obtained datasets were applied: (i) a multiomics discriminant analysis (DIABLO -Data Integration Analysis for Biomarker discovery using Latent variable approaches for Omics studies); and (ii) a multi-stage integration of features selected in differential expression analysis on each dataset and then merged. Selected molecules from the in vitro study were quantified by qPCR ex vivo in PBMCs from MS patients receiving cladribine.Results: PBMCs treated in vitro with cladribine were characterized by a major downregulation of gene, protein, and miRNA expression compared with the untreated cells. An intermediate pattern between the cladribine-treated and untreated conditions was observed in PBMCs treated with cladribine in its inactive form. The differential expression analysis of each dataset led to the identification of four genes and their encoded proteins, and twenty-two miRNAs regulating their expression, that were associated with cladribine treatment. Two of these genes (PPIF and NHLRC2), and three miRNAs (miR-21-5p, miR-30b-5p, and miR-30e-5p) were validated ex vivo in MS patients treated with cladribine. Discussion: By using a combination of omics data and bioinformatics approaches we were able to identify a multiomics molecular profile induced by cladribine in vitro in PBMCs. We also identified a number of biomarkers that were validated ex vivo in PBMCs from patients with MS treated with cladribine that have the potential to become treatment response biomarkers to this drug.